Relationship between pesticide use and climate change for crops - Palikhe, Bhakta R. (Journal of Agriculture and Environment, 2007)
The use (and abuse) of pesticides has increased to combat insect-pests and diseases. However, the major causes concern of are the undesirable side effects of these chemicals on biodiversity, environment, food quality and human health .Climate change will have important implications for insect conservation and pest status. Climate and weather can substantially influence the development and distribution of insects. Most of the warming over the last 50 years is likely to have been due to man-made activities. Anthropogenically induced climatic change arising from increasing levels of atmospheric greenhouse gases would, therefore, be likely to have a significant effect on agricultural insect pests. Current best estimates of changes in climate indicate an increase in global mean annual temperatures of 1[o] C by 2025 and 3[o]C by the end of the next century. Such increases in temperature have a number of implications for temperature-dependent insect pests. The Assessment investigates the relationship between pesticide use and climate for crops that require relatively large amounts of pesticide. This paper describes such input-driven agriculture, the problem of pests and diseases and the unsustainable agricultural practices that it leads to, and the socio-economic and health externalities resulting in farmer’s distress in pesticide hot spots. To protect ourselves, our economy, and our land from the adverse effects of climate change, we must ultimately dramatically reduce emissions of carbon dioxide and other greenhouse gases. The causes of anthropogenic climate change are broad and often difficult to address. There is no single solution to this complex problem, but numerous opportunities exist for reducing problems of climate change. The issue of climate change is one of the most profound challenges of our time, and we believe it is a challenge that can be met. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 83-91